Metal Assisted Synthesis of Cationic Sulfidobismuth Cubanes in Ionic Liquids - Knies, Maximilian (ChemistryOpen, 2020)
Bi(2)S(3) was dissolved in the presence of either AuCl/PtCl(2) or AgCl in the ionic liquids [BMIm]Cl ⋅ xAlCl(3) (BMIm=1‐n‐butyl‐3‐methylimidazolium; x=4–4.3) through annealing the mixtures at 180 or 200 °C. Upon cooling to room temperature, orange, air‐sensitive crystals of [BMIm](Bi(4)S(4))[AlCl(4)](5) (1) or Ag(Bi(7)S(8))[S(AlCl(3))(3)](2)[AlCl(4)](2) (2) precipitated, respectively. 1 did not form in the absence of AuCl/PtCl(2), suggesting an essential role of the metal cations. X‐ray diffraction on single‐crystals of 1 revealed a monoclinic crystal structure that contains (Bi(4)S(4))(4+) heterocubanes and [AlCl(4)](−) tetrahedra as well as [BMIm](+) cations. The intercalation of the ionic liquid was confirmed via solid state NMR spectroscopy, revealing unusual coupling behavior. The crystal structure of 2 consists of (Bi(7)S(8))(5+) spiro‐dicubanes, [S(AlCl(3))(3)](2−) tetrahedra triples, isolated [AlCl(4)](−) tetrahedra, and heavily disordered silver(I) cations. No cation ordering took place in 2 upon slow cooling to 100 K.